CRITICAL SUCCESS FACTORS OF EFFECTIVE DRUG DEVELOPMENT PROCESS: AN ANALYTICAL STUDY - Gahtori, Prashant (International Journal of Psychosocial Rehabilitation, 2021)
This article is aimed to describe factors which are effective towards the success of drug discovery and their development process. According to the research, there is no single explanation on behalf of this discussion as the content outlines crucial factors on its enhancement. Drug development is very critical process, because it helps to treat contemporary diseases and fight the new ones which are within the human populace. Before a drug can reach to an affected person, it should consider successful and rigorous factors that encourage the pharmaceutical developmental programs decide whether it’s far safe, powerful towards treating the severe circumstances and also help them to, envision the correct dosage as well as the suitable administration path. The mentioned factors in the below section, are several outcome of this research therefore, such theories help pharmaceutical industry to study their capability techniques and encourage them to enhance medical development fulfilment prices and its productivity also. Advancement in sciences and technology is also helping this industry with many unique processes and level, from their ideation to development to its approval. There are many pharmaceutical drug development programs which are based on a global strategy that results to predictable expedited approval outcomes.